Effectiveness Of Peltier Cooling Device In Reducing The Air Temperature Of Rooms In Buildings - Seifi, Molood (2013)
The excessive usage of air-conditioning to cool internal room in a building for human thermal comfort is harming our planet due to their hazardous refrigerants and the high energy consumption nature of these cooling systems. Hence replacement of these systems with the Peltier Cooling Device (PCDs) which are more environmental friendly is highly encouraged. However, the application of PCDs in Buildings has remained minimal as they have limited cooling capacities that reduces the ability of the device in generating cooling effect and causing temperature reduction in enclosed spaces. Thus the present study seeks to improve the temperature reduction by the Peltier Cooling Device through an appropriate application strategy so that they can be used for reducing the temperature of buildings internal spaces. The data analysis of physical experiments revealed that there is a temperature reduction improvement of 0.75-0.78 °C by each PCD operating on the internal room when the overall building temperature is dropped by 5 °C in the application strategy two (AS2). Hence this strategy is the appropriate one to enhance the ability of the device in reducing the temperature reduction of the internal room. Moreover the Malaysian thermal comfort (MTC) for each cubic meter of the building internal spaces could be fulfilled with one to five modules of PCDs in normal room temperature up to 32 ° C; while the MTC can be achieved for internal spaces of higher temperature range 33 ° C – 37 ° C when the overall room temperature is dropped by 5 ° C with the assistance of any type of cooling system, likewise the application strategy two.